RELEVANSI MANUSIA MULTIDIMENSI MURTADHA MUTHAHHARI BAGI PENDIDIKAN ISLAM - Sulhatul Habibah (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2021)
Humans have various potentials in themselves and the task of humans is to be a leader on earth. There are many obstacles to make this happen, in the era of globalization and modernization, many human behaviors are less wise. For example, in the name of religion, religion is used as a trade icon to reap a lot of profits, hoax news circulates, many Islamic teachings on social media whose sources are not clear, and so on. These problems can of course be solved through Islamic education. Islamic education is an effort to educate, grow, and develop knowledge in accordance with Islamic teachings based on the Qur'an and Hadith. The goal is to produce superior humans, intelligent humans who are able to think and be virtuous. In this paper, the author analyzes the multidimensional relevance of Murtadha Mutahhari's human being with Islamic education. Of course, to make a superior human being is very relevant to some of Mutahhari's concepts such as the human dimension which contains knowledge, ethical virtues, beauty and rituals that can build human identity with personality. Aware of his role on earth as caliph and balance both material and spiritual aspects.